Answer:
Tyler's - (-5 - 3y) + (3y) = -5
Han's - (x) + (-5 - x) = -5
Step-by-step explanation:
If we are going to use Tyler's first step then we would use x = - 5 - 3y and substitute it in the original simultaneous equation x + 3y = -5, becoming (-5 - 3y) + (3y) = - 5 giving an exact answer of - 5.
But if we are using Han's first step then we will still substitute into the original simultaneous equation but in 3y. It would become
x + (-5 - x) = - 5 which also gives us an exact answer of -5.
Thus proving that both first steps show the same solution of -5.
<span>-3s^2-s+10
= (3x - 5)(-x - 2)
hope that helps</span>
N= numerator
D= denominator
N:D ==> 2:3
2:3, 4:6, 6:9... And so on...
The pattern here is that the numerator increases by 2 and the denominator by 3. Easy right?
Now 5 is added to the "n".
Now it is N:D ==> 3:2
3:2, 6:4, 9:6... And so on...
The pattern here is inverted then the 2:3 one.
If I'm right then which one (you might have to continue the process/pattern) then one of them will increase by 5.
3 => 2 = +1 (2+1=3)
6 => 4 = +2 (4+2=6)
9 => 6 = +3 (6+3=9)
12 => 8 = +4 (8+4=12)
15 => 10 = +5 (10+5=15)
18 => 12= +6 (12+6=18)
Q. Which one is +5?
A. 15:10
That is what "I" think it is.
Now, the question is,
Does it work? Does it fit the above description?
Q. Does it even work? Does it fit the above description?
Answer:
the answer to this is 7 7/10
Answer:
7 × 10²
Step-by-step explanation:
→ The first digit has to be above 1 and below 10